Kajian Teologis 1 Petrus 5:7 tentang Perlindungan Allah terhadap Orang Percaya di Tengah Pandemi Covid-19 - Joseph Christ Santo; Yonatan Alex Arifianto (Sekolah Tinggi Alkitab Jember, 2021)
The Covid-19 pandemic has had a very heavy impact on humans to survive. The problem that is felt by all elements of society is related to the economy and the fulfilment of the necessities of life, but also the fear of being exposed to this virus haunts believers. Therefore, governments in affected countries must enact regulations that make the economy's wheels stagnate, as a result, economic problems are a serious problem in the fight against the Coronavirus. This research aims to answer how the concept of protection guarantees for believers is applied in the study of God's word, as a basis and insight to be able to survive and continue the opportunity to live in God's prerogative amidst the threat of the Covid 19 pandemic and the continuing impact that follows. With the formulation of the problem, the literature research method is used with a descriptive qualitative approach. It can be concluded that God's protection is a guarantee of God's providence that occurred in the Old and New Testament times which became the reference for the concept of God's care and protection during the pandemic period to bring believers to become obedient individuals to God by obeying the rules made by the government as a means of maintaining believers.AbstrakPandemi Covid-19 telah memberikan dampak yang sangat berat bagi manusia untuk bertahan hidup. Masalah yang dirasakan seluruh elemen masyarakat adalah berkenaan dengan ekonomi dan pemenuhan kebutuhan hidup, tetapi juga rasa kuatir akan terpapar virus ini menghantui orang percaya. Oleh sebab itu pemerintah di negara-negara terpapar harus memberlakukan peraturan yang membuat roda perekonomian tersendat, akibatnya masalah ekonomi menjadi problem yang serius dalam upaya melawan virus Corona. Peneli-tian ini bertujuan untuk menjawab bagaimana penerapankonsep jaminan perlin-dungan bagi orang percaya dalam kajian firman Tuhan, sebagai dasar dan wawasan untuk dapat bertahan dan melanjutkan kesempatan hidup dalam prerogatif Allah di tengah ancaman pandemi Covid 19 dan dampak berkelanjutan yang mengikutinya. Dengan rumusan masalah tersebut, maka digunakan metode penelitian pustaka dengan pendekatan kualitatif deskriptif. Disimpulkan bahwa God’s protection adalah jaminan pemeliharaan Tuhan yang terjadi dalam masa Perjanjian Lama dan Perjanjian Baru yang menjadi acuan konsep pemeliharaan dan proteksi Allah pada masa pandemi untuk membawa orang percaya menjadi pribadi yang taat kepada Tuhan dengan menaati aturan yang dibuat pemerintah sebagai sarana untuk meme-lihara orang percaya.